«El espíritu de asociación católica lo está invadiendo todo»: Joaquín Larraín Gandarillas en Estados Unidos (1851-1852). - MALDONADO ARAYA, Matías (Humanidades: Revista de la Universidad de Montevideo, 2022)
The article analyzes the impressions of the Chilean priest Joaquín Larraín Gandarillas during his stay in the United States in 1851-1852. It highlights that Larraín considered Catholic associations to be the most attractive feature of American Catholicism and believed they could act as a barrier to stop the spread of revolutionary ideas in Chile. The article also emphasizes the importance of American Catholicism as a model for the Catholic Church in Latin American republics during the 19th century. Additionally, it mentions other works related to Larraín's role as rector of the Seminary and the Catholic University of Santiago.